Prevention of Child Labor Exploitation Through the Implementation of Fair Labor Laws - Siti Nurhayati; Elly Asmarawati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Many companies still employ “child labor,” and the number of child workers who require a legal protection system continues to increase. This makes it highly interesting to examine and study how the legal protection of child workers from labor exploitation is actually implemented. Therefore, the central issue of this thesis can be formulated as follows: how is the implementation of labor laws carried out as a legal protection effort against the exploitation of child workers, and what obstacles and measures have been taken by the government to address child labor exploitation. This research is a type of normative juridical study, which is a library-based study focusing on secondary data, including an inventory of positive law. Based on the research results, it can be described that the existing legal protection system for child workers has not been implemented effectively. Legal violations committed by employers do not receive the appropriate legal actions due to the non-performance of labor inspection officers’ functions. Therefore, it is necessary to strive for a unified determination and coordinated actions from government officials, implementing officers, employers, parents, and all components of the nation to genuinely eliminate child labor.